Overview of Compliance in Filling-in Initial Nursing Assessment by Nurses in Hospital - Vinna Melindayanti; Kholid Rosyidi Muhammad Nur; Alfid Tri Afandi; Ika Mardiyah Bratajaya (Health and Technology Journal (HTechJ), 2025)
The initial nursing assessment is a holistic record of the patient's condition and needs, which is used as a reference to determine effective and appropriate nursing interventions for the patient. Incomplete filling can affect the quality of health services provided to patients. This research aims to determine the description of compliance in filling out the initial nursing assessment by nurses at the hospital. This research was conducted from 21-26 October 2024 with a sample size of 68 medical record files. The design of this research is descriptive research. The results of this study show that of the eight components examined in this study, it was found that the highest level of completeness in filling out the initial nursing assessment form was in the physical assessment component of the patient, namely 35 medical records (51.4%), as well as the general assessment and assessment of the patient's medical history, namely as many as 33 medical records (48.5%). The component with the lowest completeness is the Gordon pattern assessment component, namely, zero medical records. The percentage of compliance for nurses is 89.7%, with the number of initial nursing assessment files being 61 files. This shows that the nurses are still not compliant in documenting the initial nursing assessment.